Difficulties and fears of nurses facing the COVID-19 pandemic in Brazil - Vagner Ferreira Nascimento; Thalise Yuri Hattori; Ana Cláudia Pereira Terças-Trettel (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Introduction: The high transmissibility and expansion of the new coronavirus (SARS-CoV-2) in the world constitute a high occupational risk for health professionals, especially nurses. Objective: To identify the difficulties and fears of nurses facing the COVID-19 pandemic in Brazil. Methods: This is an exploratory and qualitative study, carried out in March 2020, with nurses from various health institutions. The data collection was done through the WhatsApp application, with a questionnaire. Content analysis was used for data analysis. Results: The difficulties and fears presented were related to the daily risk of exposure to the virus, problems of access and use of personal protective equipment, doubts in the differential diagnosis as well as work overload and the increased demand for care with patients and relatives. Discussion: The vulnerability of the nurses in the study is worrying, since they lack support and care, they interfere with health and the quality of care. This sum of factors increases the fear, anxiety, insecurity and uncertainty facing the future.